2021
DOI: 10.1111/imr.13036
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and tissue immunity—Translating environmental cues into functional adaptations*

Abstract: Tissue immune responses require the coordinated activation of specialized cell types, both professional immune cells and organ structural cells, each with differing, but tightly regulated, transcriptional programmes that are switched on and off in response to pathogen or tissue damage signals. The precise immune functionality of these tissue populations is determined by the selection of genes they express, encoding proteins that differentially contribute to immune responses. Tissue immune cells encounter an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 307 publications
(330 reference statements)
0
6
0
Order By: Relevance
“…Continuing technological advances would enable a deeper understanding of the epigenetic mechanisms that control the recruitment, polarization, and activation of immune cells in response to cigarette smoke and allergen co-stimuli at single-cell resolution, and their application in combination with multi-omic strategies to ACO has the potential to identify cell- and tissue-specific epigenetic targets for disease treatments across organs. Integrating all genome and different types of epigenetic alteration data may help to reveal the regulatory role of epigenetics in the formation of ACO more comprehensively [ 90 ]. Clinically, the evaluation and modulation of epigenetics manifest as promising prospects in the diagnosis and treatment of ACO.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing technological advances would enable a deeper understanding of the epigenetic mechanisms that control the recruitment, polarization, and activation of immune cells in response to cigarette smoke and allergen co-stimuli at single-cell resolution, and their application in combination with multi-omic strategies to ACO has the potential to identify cell- and tissue-specific epigenetic targets for disease treatments across organs. Integrating all genome and different types of epigenetic alteration data may help to reveal the regulatory role of epigenetics in the formation of ACO more comprehensively [ 90 ]. Clinically, the evaluation and modulation of epigenetics manifest as promising prospects in the diagnosis and treatment of ACO.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions influence their epigenetic landscape, allowing for tissue-specific adaptations. 19,122 For example, it has been demonstrated that the gut microbiome influences the epigenetic landscape of ILCs in the small intestine, resulting in phenotypical and functional differences. 123 In support of this hypothesis, Nussbaum et al showed that the effector functions of type 3 ILCs were largely influenced by the tissue of residence and not solely by the tissue of origin.…”
Section: Trafficking and Tissue-residencymentioning
confidence: 99%
“…The development and survival of ILCs require a coordinated interplay between the epithelial and stromal cells of the tissue and the tissue‐resident immune cells. These interactions influence their epigenetic landscape, allowing for tissue‐specific adaptations 19,122 . For example, it has been demonstrated that the gut microbiome influences the epigenetic landscape of ILCs in the small intestine, resulting in phenotypical and functional differences 123 .…”
Section: Nk Cell‐intrinsic Epigenetic Regulation Of Survivalmentioning
confidence: 99%
“…The transmitted epigenetic changes may reflect environmental adaptations made by the parent and transmitted to the offspring through the germline ( 28 , 35 , 180 , 181 ). The offspring of male mice who have been fed a low-protein diet inherit epigenetic marks that affect the peroxisome proliferator-activated receptor alpha (PPARA) gene which regulates lipid and cholesterol metabolism ( 180 ).…”
Section: Transgenerational Inheritance Of Epigenetic Marksmentioning
confidence: 99%